THE IMPORTANCE OF COST MANAGEMENT IN A MANUFACTURING COMPANY OF HYDROELECTRIC PLANTS - A CASE STUDY - Mello, Mario Fernando (2016)
Abstract: Changes in the global market happen at all times and the update of the companies must be constant and rapid, thus it is necessary that managers are aware of the current status of the organization and its projects, mainly in cost sector. This paper aims to demonstrate the importance of cost managements and proposes a design methodology, through an applicative program for an appropriate management of costs in the studied company.  The research occurred in the hydro sector on an assembly company of hydroelectric plants in the state of Rio Grande do Sul, Brazil. The survey results showed the importance of cost control in each project and this topic is part of the company financial policy. The results of this study show that a methodological structuring of cost control is vital for managers to have reports at hand in a proper sequence information, that is relevant to make decisions.